1974
DOI: 10.1590/s0074-02761974000200004
|View full text |Cite
|
Sign up to set email alerts
|

Estudos de cestóides de peixes do Brasil

Abstract: Os autores iniciam com este trabalho um estudo sistemático de determinação dos cestóides de peixes depositados na Coleção helmintológica do Instituto Oswaldo Cruz. São referidas ou descritas as seguintes espécies e seus hospedeiros: Schizochoerus liguloideus (Diesing, 1850) e Nesolecithus janicki Posche, 1922, ambas de Arapaima gigas (Cuvier), (piracuru); Gyrocotyle meandrica Herrera, 1946, de Callorhynchus callorhynchus (L.), (quimera); Acanthobothrium dasybati Yamaguti, 1934 e Pterobothriidae não identificad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
4

Year Published

1985
1985
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 0 publications
1
34
0
4
Order By: Relevance
“…(1974). CHAMBRIER & VAYCHER (1997) reexamined the type material of this species and concluded that is a composite species, specimens of Prateocephalus mixed with Monticellia; they proposed the name Monticellia magna (Rego, Santos & Silva, 1974) comb.n., but they failed to name the Proteocephalus specimens.…”
Section: Palllicea Llletkenimentioning
confidence: 99%
See 2 more Smart Citations
“…(1974). CHAMBRIER & VAYCHER (1997) reexamined the type material of this species and concluded that is a composite species, specimens of Prateocephalus mixed with Monticellia; they proposed the name Monticellia magna (Rego, Santos & Silva, 1974) comb.n., but they failed to name the Proteocephalus specimens.…”
Section: Palllicea Llletkenimentioning
confidence: 99%
“…Synonyms: Monticellia siluri (Fuhrmann, 1916) Woodland, 1925. FREZE (1965 gives "Corallobothriurn siluri (Fuhrmann, 1916), Harwood, 1933" as REGO et a!. (1974), BROOKS & DEARDORFF (1980).…”
Section: Goezeella Nupeliensismentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was based on critical observations of features in most proteocephalidean genera studied by the present authors: A.A. Rego and A. de Chambrier in South America (see Rego et al, 1974;de Chambrier & Vaucher, 1984Rego, 1987Rego, , 1991Rego, , 1994de Chambrier, 1987de Chambrier, , 1988de Chambrier, , 1989ade Chambrier, ,b, 1990Rego & Pavanelli, 1990de Chambrier et al, , 1996de Chambrier & Paulino, 1997;de Chambrier & Rego, 1994Scholz et al, 1996) and V. Hanzelová & T. Scholz in the Holarctic (Scholz, 1989(Scholz, , 1991(Scholz, , 1993Scholz & Ergens, 1990;Hanzelová & Spakulová, 1992;Hanzelová & Scholz, 1992Scholz & Cappellaro, 1993;Scholz & Hanzelová, 1994;Hanzelová et al, 1995a,b;Scholz et al, 1995Scholz et al, , 1997.…”
Section: Specimens Examinedmentioning
confidence: 99%
“…Further investigations have been carried out at the subtropical Southwest Brazilian coast (Mendes 1944, Rego et al 1974, Pissaia Saciloto 1980, Pereira et al 1982, Carvajal & Rego 1983, São Clemente 1982, 1986a,b, São Clemente & Gomes 1989a,b, 1992, São Clemente et al 1991. However, all are observations on only one or a few parasite species and Palm (1995) gave no data concerning parasite abundance and prevalence of infestation.…”
mentioning
confidence: 99%